Method for preparing magnetic wrinkled graphene oxide adsorption material and application of magnetic wrinkled graphene oxide adsorption material

The preparation of magnetic wrinkled graphene oxide adsorption materials by electrochemical method solves the problem of using toxic raw materials and process complexity in the prior art, and achieves a green, simple and efficient preparation process and good adsorption performance.

CN119633748APending Publication Date: 2025-03-18NINGBO GRAPHENE INNOVATION CENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411733275.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing methods for preparing wrinkled graphene oxide adsorption materials usually require the use of toxic and harmful raw materials, and the preparation process is complex, the cost is high, and the process is complex.

Method used

The edge graphite oxide intercalation mixture was prepared by electrochemical method, and magnetic wrinkled graphene oxide adsorption material was prepared through electrochemical oxidation and peeling, cleaning and ultrasonic dispersion. This method avoids the preparation of high and low temperatures, simplifies the process flow, and reduces the risk of using toxic raw materials.

Benefits of technology

The preparation of magnetic wrinkled graphene oxide adsorbent materials has been achieved in green, simple and efficient. The material has good adsorption performance and reusable ability, and is suitable for environmental protection and composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633748A_ABST
    Figure CN119633748A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a magnetic wrinkled graphene oxide adsorption material and application thereof. The method comprises the following steps: preparing an edge graphite oxide intercalation mixture in a vacuum environment by using a dual-electrode system; taking the obtained edge graphite oxide intercalation mixture as a working electrode, taking a platinum wire as a counter electrode, and then putting the edge graphite oxide intercalation mixture and the platinum wire into a Ba (OH) 2 solution for electrochemical oxidation and stripping to obtain graphene oxide; stirring the obtained graphene oxide dispersed in the solution, enabling Ba < 2 + > and HSO4 <-> to finally generate BaSO4 precipitate in the solution, and separating the graphene oxide through centrifugation; the preparation method comprises the following steps: ultrasonically dispersing graphite oxide in water to prepare a graphene oxide dispersion liquid, dropwise adding the graphene oxide dispersion liquid into absolute ethyl alcohol, then adding a magnetic material, stirring under the ultrasonic action, and freeze-drying the mixed solution to obtain a magnetic wrinkled graphene oxide adsorption material; the method has the advantages of greenness, simplicity, convenience and high efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of graphene oxide preparation, and particularly relates to a method for preparing a magnetic wrinkled graphene oxide adsorption material and application thereof. Background Art

[0002] Graphene oxide (GO) is a derivative of graphene with many excellent properties. Unlike graphene, GO has sp 2 Outside the hybrid region, there are also a lot of sp 3 The oxidation process destroys the sp 2 -sp 2 The hybrid structure increases the distance between GO layers in graphite. GO contains a large number of oxygen-containing groups and defects. Hydroxyl and epoxy groups are mainly distributed inside the sheets of graphite oxide, while carbonyl and carboxyl groups are mainly distributed at the edges. GO has the advantages of large specific surface area, good chemical stability, excellent mechanical properties, optical properties and thermal conductivity. While having a similar structure to graphene, its surface also contains a large number of oxygen-containing functional groups. In addition, GO has good water dispersibility and modifiability, and is inexpensive and easy to obtain. Therefore, it is widely used in biomedicine, building materials, environmental protection, energy storage devices, anti-corrosion coatings and other fields.

[0003] In order to make GO have better properties, wrinkling and magnetization are commonly used methods to modify GO. The current methods for preparing wrinkled GO usually require toxic and harmful ammonia water as raw material, and most of them need to be prepared at extremely low or extremely high temperatures, which is dangerous. In addition, these preparation methods are often complicated and require the use of multiple equipment. In addition, wrinkling and magnetization modification of GO are usually carried out in steps, which increases the preparation cost, time and process complexity. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present application provides a green, simple and efficient method for preparing magnetic wrinkled graphene oxide adsorption material.

[0005] In order to solve the above technical problems, the technical solution adopted in this application is: a method for preparing a magnetic wrinkled graphene oxide adsorption material, the preparation steps comprising:

[0006] (1) Preparation of edge oxidation graphite intercalation mixture (EGOIC): The preparation of EGOIC by electrochemical edge oxidation intercalation is carried out using a two-electrode system in a vacuum environment, with graphite as the working electrode (anode) and platinum wire as the counter electrode (cathode). The graphite and platinum wire are then placed in a H2SO4 solution in parallel. A constant voltage is applied by a regulated DC power supply for edge oxidation. A small amount of OH in water in the H2SO4 solution is -The ions gradually oxidize the graphite edge and open the graphite edge interlayer spacing until no bubbles are generated; then a constant voltage is applied for intercalation reaction, HSO4 - Gradually inserted into the graphite interlayer, the graphite gradually expands and turns blue, until the graphite turns completely blue, that is, the edge oxide graphite intercalation mixture (EGOIC) is obtained;

[0007] (2) Oxidation and exfoliation of edge oxide graphite intercalation mixture (EGOIC): The EGOIC obtained in step (1) is used as the working electrode (anode) and the platinum wire is used as the counter electrode (cathode). The EGOIC and the platinum wire are then placed in a Ba(OH)2 solution in parallel. A constant voltage is applied using a regulated DC power supply to electrochemically oxidize and exfoliate the EGOIC. As the reaction proceeds, the graphene oxide gradually falls off and disperses in the solution until the EGOIC is completely exfoliated and the reaction stops.

[0008] (3) Cleaning of graphene oxide: The graphene oxide dispersed in the solution obtained in step (2) is stirred. 2+ and HSO4 - Finally, BaSO4 precipitate is generated in the solution, and stirring is stopped until no more precipitation is generated in the solution; then, graphene oxide is separated by centrifugation (BaSO4 and GO have different densities, which will produce stratification, GO is dispersed in the supernatant, and BaSO4 is precipitated at the bottom, so the two can be separated by centrifugation to separate BaSO4 and GO), and washed to remove residual impurities;

[0009] (4) Preparation of magnetic wrinkled graphene oxide adsorbent material: The cleaned graphite oxide obtained in step (3) is ultrasonically dispersed in water to prepare a graphene oxide dispersion, the graphene oxide dispersion is dropwise added into anhydrous ethanol, and then the magnetic material is added, stirred under ultrasonic action to react, and then the mixed solution is freeze-dried to obtain a magnetic wrinkled graphene oxide adsorbent material (MFGO).

[0010] Furthermore, the usage ratio of the graphite and the H2SO4 in step (1) is 0.3-0.9 g: 90-120 mL (the specific amount can be increased or decreased in proportion according to the ratio).

[0011] Furthermore, the concentration of H2SO4 in step (1) is 80-90wt.%.

[0012] Furthermore, in step (1), the constant voltage applied for edge oxidation is 10-15V; and the constant voltage applied for intercalation reaction is 3-5V.

[0013] Furthermore, in step (2), the usage ratio of the edge oxide graphite intercalation mixture (EGOIC) to the Ba(OH)2 solution is 0.1-0.3 g: 100-200 mL (specifically, the usage ratio can be increased or decreased in proportion according to the ratio).

[0014] Furthermore, in step (2), the concentration of the Ba(OH)2 solution is 0.05-0.2 mol / L.

[0015] Furthermore, in step (2), the constant voltage applied is 8-12V.

[0016] Furthermore, in step (3), the stirring speed is 300-600 r / min, and the centrifugal speed is 500-1000 r / min.

[0017] Furthermore, in step (4), the usage ratio of the graphene oxide dispersion, the magnetic material, and anhydrous ethanol is 33-150 mL: 0.2-0.9 g: 22-600 mL (specifically, the ratio can be proportionally increased or decreased according to the ratio).

[0018] Furthermore, in step (4), the concentration of the graphene oxide dispersion is 2-3 mg / mL.

[0019] Furthermore, in step (4), the volume ratio of the graphene oxide dispersion to anhydrous ethanol is 0.25-1.5:1.

[0020] Furthermore, the magnetic material described in step (4) is at least one of Fe3O4, NiO, and CoO.

[0021] Furthermore, in step (4), the stirring time is 5-15 min.

[0022] The present application also provides an application of the magnetic wrinkled graphene oxide adsorption material prepared as above, specifically, such as use in the fields of environmental protection, composite materials, etc.

[0023] Advantages and beneficial effects of this application:

[0024] (1) The present invention provides a method for rapidly preparing GO based on an electrochemical method, which has the significant advantages of being safe, rapid, simple and easy to operate.

[0025] (2) The method of edge oxidation intercalation and stripping in steps provided by the present invention can improve the intercalation efficiency and effectively avoid the problems of uneven intercalation and insufficient oxidation.

[0026] (3) The present invention uses BaSO4 as the electrolyte in the oxidation stripping stage, which can not only effectively oxidize and strip GO, but also remove HSO4 in the EGOIC precursor. - , which greatly reduces the amount of water required for cleaning.

[0027] (4) The present invention provides a one-step method (i.e., wrinkling and magnetization modification are completed in one step) for preparing MFGO, which has the significant advantages of being fast, efficient, green, environmentally friendly, and simple and easy to operate.

[0028] (5) The MFGO prepared in the present invention is used as an adsorbent to effectively remove pollutants in water and is easy to separate.

[0029] (6) The present application performs wrinkling treatment on graphene oxide prepared by a specific process. Compared with non-wrinkled graphene oxide, wrinkled graphene oxide can better load magnetic materials, thereby making wrinkled graphene oxide magnetic. When it is used to adsorb materials, it can withstand magnetism for separation and can be recycled many times. In the scheme of the present application, anhydrous ethanol is used as a poor solvent for graphene oxide. Under the action of anhydrous ethanol, graphene oxide will form a large number of wrinkles. This method avoids high-temperature and low-temperature preparation steps, is safer and more reliable, and does not require complicated equipment and operating procedures. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a physical picture of MFGO aqueous dispersion.

[0031] Figure 2 This is a physical picture of the adsorption and separation of MFGO.

[0032] Figure 3 is the X-ray diffraction pattern of MFGO.

[0033] Figure 4 This is the adsorption performance diagram of MFGO for MB. DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with specific embodiments, but the technical solutions of the present application are not limited to the following embodiments.

[0035] Embodiment 1:

[0036] Step 1: Preparation of edge oxidation graphite intercalation mixture (EGOIC): The preparation of EGOIC by electrochemical edge oxidation intercalation is carried out using a two-electrode system in a vacuum environment, with graphite as the working electrode (anode) and platinum wire as the counter electrode (cathode). Then, 0.6 g of the graphite working electrode and the platinum wire counter electrode are placed in 120 mL of 85 wt.% H2SO4 solution, and the two are placed in parallel. A regulated DC power supply is used to apply a constant voltage of 12.5 V for edge oxidation. A small amount of OH in water in the H2SO4 solution is used to react with the graphite working electrode and the platinum wire counter electrode. - The ions gradually oxidize the graphite edge and open the graphite edge interlayer spacing until no bubbles are generated; then a constant voltage of 4V is applied for intercalation reaction, HSO4 - Gradually inserted into the graphite layers, the graphite gradually expands and turns blue, until the graphite turns completely blue, and EGOIC is obtained.

[0037] The constant voltage of 12.5V is applied for edge oxidation until no bubbles are generated. This process mainly oxidizes the edge of graphite by electrolyzing water in sulfuric acid. The generated gas can further expand the edge of graphite.

[0038] No bubbles are generated, indicating that the water in the sulfuric acid is electrolyzed and no gas is generated. At this time, the sulfuric acid is a high-concentration sulfuric acid with extremely low water content. Then a constant voltage of 4V is applied to perform the intercalation reaction. (High-concentration sulfuric acid has a better intercalation effect)

[0039] The reaction is carried out in a vacuum environment because after the edge oxidation reaction is completed, 80-90wt.% of H2SO4 turns into high-concentration sulfuric acid. High-concentration sulfuric acid has strong water absorption, and high-concentration sulfuric acid can be prevented from absorbing water in a vacuum environment.

[0040] Step 2: Oxidation and stripping of EGOIC: Electrochemical oxidation and stripping of EGOIC are carried out using a two-electrode system. Take 0.2g of EGOIC obtained in step 1 as the working electrode (anode) and platinum wire as the counter electrode (cathode). Then put EGOIC and platinum wire into 150mL of Ba(OH)2 solution with a concentration of 0.1mol / L, and place them in parallel. A constant voltage of 10V is applied with a regulated DC power supply to electrochemically oxidize and strip EGOIC. As the reaction proceeds, GO gradually falls off and disperses in the solution until EGOIC is completely stripped and the reaction stops.

[0041] The use of barium hydroxide not only achieves the effect of stripping preparation, but also plays the role of deacidification, making the cleaning step more convenient and quicker, saving energy. It is equivalent to the fact that barium hydroxide has the function of deacidification, making cleaning convenient, and reducing the amount of water used for cleaning.

[0042] Step 3: GO cleaning: The GO dispersed in the solution obtained in step 2 was stirred at a speed of 450 r / min. 2+ and HSO4- BaSO4 precipitate is finally generated in the solution, and stirring is stopped until no more precipitate is generated in the solution. GO is separated by centrifugation at a speed of 750r / min and washed with water to remove residual impurities. - It is ultimately removed in the form of BaSO4 precipitation, greatly reducing the amount of water required for cleaning.

[0043] Step 4: Preparation of MFGO: Ultrasonic dispersion of 0.2 g of the washed GO powder obtained in step 3 in water to prepare 80 ml of graphene oxide dispersion; the obtained graphene oxide dispersion is added dropwise into 120 ml of anhydrous ethanol, and then 0.4 g of Fe3O4 magnetic material is added, stirred under ultrasonic action for 10 min, and then the mixed solution is freeze-dried to obtain MFGO.

[0044] The addition of magnetic materials can make wrinkled graphene oxide magnetic; wrinkled graphene oxide can load magnetic materials better than wrinkled graphene oxide.

[0045] Anhydrous ethanol is a poor solvent for graphene oxide. Under the action of anhydrous ethanol, graphene oxide will form a large number of wrinkles; this method avoids the high and low temperature preparation steps, is safer and more reliable, and does not require complicated equipment and operating procedures.

[0046] Taking the MFGO prepared in Example 1 as an example, characterization and performance determination were carried out, and methylene blue (MB), a typical pollutant, was selected as the target pollutant to study the adsorption performance of MFGO on MB:

[0047] Figure 1 This is a physical picture of the aqueous dispersion of MFGO prepared in Example 1 of the present application. It can be seen from the figure that MFGO can be evenly dispersed in water, which shows that MFGO contains abundant hydrophilic groups and also illustrates the feasibility and advantages of MFGO as an adsorbent to treat pollutants in water.

[0048] Figure 2 This is a physical picture of the adsorption and separation of MFGO prepared in Example 1 of the present application. From the figure, it can be seen that the MFGO adsorbed with MB is gathered together under the action of the magnet, indicating that the magnetic material is successfully loaded into MFGO, and also reflects the advantage of MFGO being easy to separate.

[0049] Figure 3 This is the X-ray diffraction pattern of MFGO prepared in Example 1 of the present application. Figure 3As shown, there is a characteristic peak of GO at 9.5°, and typical peaks of Fe3O4 at diffraction angles of about 30.1°, 36.2°, 43.0°, 56.9° and 62.4°, which indicates that Fe3O4 is successfully loaded into the MFGO material.

[0050] Figure 4 This is a graph showing the adsorption performance of MB by MFGO prepared in Example 1 of the present application. Figure 4 a, 4b, and 4c are the adsorption performance diagrams of MB on MFGO at different pH, different temperatures, and different cycle times. Figure 4 It can be seen from a that as the pH value of the solution increases, the adsorption capacity of MFGO for MB increases. Moreover, in the pH range of 3-9, MFGO exhibits good adsorption capacity for MB, indicating that MFGO can be used as an adsorbent in wastewater with different pH values ​​and has a wide range of applications. Figure 4 As can be seen in b, temperature will change the equilibrium capacity of MFGO to adsorb MB. As the temperature increases, the adsorption performance decreases, but the degree of change is not large, and a high adsorption can be achieved at room temperature. The cycle stability and cycle number of the adsorbent are very important. Figure 4 c It can be seen that the initial adsorption capacity is 387.40 mg / g. After 7 consecutive cycles, the adsorption capacity of MFGO is 325.61 mg / g, and the adsorption capacity is 84% ​​of the initial value, indicating that the MFGO prepared in this application has good reusability.

[0051] Example 2

[0052] Step 1: Preparation of edge oxidation graphite intercalation mixture (EGOIC): The preparation of EGOIC by electrochemical edge oxidation intercalation is carried out using a two-electrode system in a vacuum environment, with graphite as the working electrode (anode) and platinum wire as the counter electrode (cathode). Then, 0.9g of the graphite working electrode and the platinum wire counter electrode are placed in 150mL of 85wt.% H2SO4 solution, and the two are placed in parallel. A regulated DC power supply is used to apply a constant voltage of 12.5V for edge oxidation. A small amount of OH in water in the H2SO4 solution is used to react with the graphite working electrode and the platinum wire counter electrode. - The ions gradually oxidize the graphite edge and open the graphite edge interlayer spacing until no bubbles are generated; then a constant voltage of 4V is applied for intercalation reaction, HSO4 - Gradually inserted into the graphite layers, the graphite gradually expands and turns blue, until the graphite turns completely blue, and EGOIC is obtained.

[0053] Step 2: Oxidation and stripping of EGOIC: Electrochemical oxidation and stripping of EGOIC are carried out using a two-electrode system. Take 0.3g of EGOIC obtained in step 1 as the working electrode (anode) and the platinum wire as the counter electrode (cathode). Then put EGOIC and the platinum wire into 150mL of a Ba(OH)2 solution with a concentration of 0.1mol / L, and place them in parallel. A constant voltage of 10V is applied with a regulated DC power supply to electrochemically oxidize and strip EGOIC. As the reaction proceeds, GO gradually falls off and disperses in the solution until EGOIC is completely stripped and the reaction stops.

[0054] Step 3: GO cleaning: The GO dispersed in the solution obtained in step 2 was stirred at a speed of 500 r / min. 2+ and HSO4 - BaSO4 precipitate is finally generated in the solution, and stirring is stopped until no more precipitate is generated in the solution. GO is separated by centrifugation at a speed of 720r / min and washed with water to remove residual impurities. - It is ultimately removed in the form of BaSO4 precipitation, greatly reducing the amount of water required for cleaning.

[0055] Step 4: Preparation of MFGO: Ultrasonic dispersion of 0.2 g of the washed GO powder obtained in step 3 in water to prepare 80 ml of graphene oxide dispersion; the obtained graphene oxide dispersion is added dropwise into 120 ml of anhydrous ethanol, and then 0.4 g of Fe3O4 magnetic material is added, stirred under ultrasonic action for 10 minutes, and then the mixed solution is freeze-dried to obtain MFGO.

[0056] Taking the MFGO prepared in Example 2 as an example, the typical pollutant methylene blue (MB) was selected as the target pollutant, and the adsorption performance of MFGO on MB was studied: the results showed that its initial adsorption capacity was 362.85 mg / g, and the adsorption capacity after 7 consecutive cycles was 301.67 mg / g.

[0057] Example 3

[0058] Step 1: Preparation of edge oxidation graphite intercalation mixture (EGOIC): The preparation of EGOIC by electrochemical edge oxidation intercalation is carried out using a two-electrode system in a vacuum environment, with graphite as the working electrode (anode) and platinum wire as the counter electrode (cathode). Then, 0.3g of the graphite working electrode and the platinum wire counter electrode are placed in 90mL of 85wt.% H2SO4 solution, and the two are placed in parallel. A regulated DC power supply is used to apply a constant voltage of 12.5V for edge oxidation. A small amount of OH in water in the H2SO4 solution is used to react with the graphite working electrode and the platinum wire counter electrode. -The ions gradually oxidize the graphite edge and open the graphite edge interlayer spacing until no bubbles are generated; then a constant voltage of 4V is applied for intercalation reaction, HSO4 - Gradually inserted into the graphite layers, the graphite gradually expands and turns blue, until the graphite turns completely blue, and EGOIC is obtained.

[0059] Step 2: Oxidation and stripping of EGOIC: Electrochemical oxidation and stripping of EGOIC are carried out using a two-electrode system, with 0.2 g of EGOIC obtained in step 1 as the working electrode (anode) and a platinum wire as the counter electrode (cathode). Then, EGOIC and the platinum wire are placed in 150 mL of a 0.1 mol / L Ba(OH)2 solution, and the two are placed in parallel. A constant voltage of 10 V is applied with a regulated DC power supply to electrochemically oxidize and strip EGOIC. As the reaction proceeds, GO gradually falls off and disperses in the solution until EGOIC is completely stripped and the reaction stops.

[0060] Step 3: GO cleaning: The GO dispersed in the solution obtained in step 2 was stirred at a speed of 500 r / min. 2+ and HSO4 - BaSO4 precipitate is finally generated in the solution, and stirring is stopped until no more precipitate is generated in the solution. GO is separated by centrifugation at a speed of 720r / min and washed with water to remove residual impurities. - It is ultimately removed in the form of BaSO4 precipitation, greatly reducing the amount of water required for cleaning.

[0061] Step 4: Preparation of MFGO: Ultrasonic dispersion of 0.2 g of the washed GO powder obtained in step 3 in water to prepare 80 ml of graphene oxide dispersion; the obtained graphene oxide dispersion is added dropwise into 120 ml of anhydrous ethanol, and then 0.4 g of magnetic material is added, stirred under ultrasonic action for 10 min, and then the mixed solution is freeze-dried to obtain MFGO.

[0062] Taking the MFGO prepared in Example 3 as an example, the typical pollutant methylene blue (MB) was selected as the target pollutant, and the adsorption performance of MFGO on MB was studied: the results showed that its initial adsorption capacity was 380.94 mg / g, and the adsorption capacity after 7 consecutive cycles was 318.78 mg / g.

[0063] Example 4

[0064] Step 1: Preparation of edge oxidation graphite intercalation mixture (EGOIC): The preparation of EGOIC by electrochemical edge oxidation intercalation is carried out using a two-electrode system in a vacuum environment, with graphite as the working electrode (anode) and platinum wire as the counter electrode (cathode). Then, 0.6 g of the graphite working electrode and the platinum wire counter electrode are placed in 120 mL of 85 wt.% H2SO4 solution, and the two are placed in parallel. A regulated DC power supply is used to apply a constant voltage of 12.5 V for edge oxidation. A small amount of OH in water in the H2SO4 solution is used to react with the graphite working electrode and the platinum wire counter electrode. - The ions gradually oxidize the graphite edge and open the graphite edge interlayer spacing until no bubbles are generated; then a constant voltage of 4V is applied for intercalation reaction, HSO4 - Gradually inserted into the graphite layers, the graphite gradually expands and turns blue, until the graphite turns completely blue, and EGOIC is obtained.

[0065] Step 2: Oxidation and stripping of EGOIC: The electrochemical oxidation and stripping of EGOIC is carried out using a two-electrode system, with 0.2g of EGOIC obtained in step 1 as the working electrode (anode) and a platinum wire as the counter electrode (cathode). Then, the EGOIC and the platinum wire are placed in 200mL of a 0.1mol / L Ba(OH)2 solution, and the two are placed in parallel. A constant voltage of 10V is applied with a regulated DC power supply to electrochemically oxidize and strip the EGOIC. As the reaction proceeds, GO gradually falls off and disperses in the solution until the EGOIC is completely stripped and the reaction stops.

[0066] Step 3: GO cleaning: The GO dispersed in the solution obtained in step 2 was stirred at a speed of 500 r / min. 2+ and HSO4 - BaSO4 precipitate is finally generated in the solution, and stirring is stopped until no more precipitate is generated in the solution. GO is separated by centrifugation at a speed of 800r / min and washed with water to remove residual impurities. - It is ultimately removed in the form of BaSO4 precipitation, greatly reducing the amount of water required for cleaning.

[0067] Step 4: Preparation of MFGO: Ultrasonic dispersion of 0.2 g of the washed GO powder obtained in step 3 in water to prepare 80 ml of graphene oxide dispersion; the obtained graphene oxide dispersion is added dropwise into 120 ml of anhydrous ethanol, and then 0.4 g of NiO magnetic material is added, stirred under ultrasonic action for 10 minutes, and then the mixed solution is freeze-dried to obtain MFGO.

[0068] Taking the MFGO prepared in Example 4 as an example, the typical pollutant methylene blue (MB) was selected as the target pollutant, and the adsorption performance of MFGO on MB was studied: the results showed that its initial adsorption capacity was 379.83 mg / g, and the adsorption capacity after 7 consecutive cycles was 316.59 mg / g.

[0069] Example 5

[0070] Step 1: Preparation of edge oxidation graphite intercalation mixture (EGOIC): The preparation of EGOIC by electrochemical edge oxidation intercalation is carried out using a two-electrode system in a vacuum environment, with graphite as the working electrode (anode) and platinum wire as the counter electrode (cathode). Then, 0.6 g of the graphite working electrode and the platinum wire counter electrode are placed in 120 mL of 85 wt.% H2SO4 solution, and the two are placed in parallel. A regulated DC power supply is used to apply a constant voltage of 12.5 V for edge oxidation. A small amount of OH in water in the H2SO4 solution is used to react with the graphite working electrode and the platinum wire counter electrode. - The ions gradually oxidize the graphite edge and open the graphite edge interlayer spacing until no bubbles are generated; then a constant voltage of 4V is applied for intercalation reaction, HSO4 - Gradually inserted into the graphite layers, the graphite gradually expands and turns blue, until the graphite turns completely blue, and EGOIC is obtained.

[0071] Step 2: Oxidation and stripping of EGOIC: The electrochemical oxidation and stripping of EGOIC is carried out using a two-electrode system, with 0.2g of EGOIC obtained in step 1 as the working electrode (anode) and a platinum wire as the counter electrode (cathode). Then, the EGOIC and the platinum wire are placed in 100mL of a Ba(OH)2 solution with a concentration of 0.1mol / L, and the two are placed in parallel. A constant voltage of 10V is applied with a regulated DC power supply to electrochemically oxidize and strip the EGOIC. As the reaction proceeds, GO gradually falls off and disperses in the solution until the EGOIC is completely stripped and the reaction stops.

[0072] Step 3: GO cleaning: The GO dispersed in the solution obtained in step 2 was stirred at a speed of 500 r / min. 2+ and HSO4 - BaSO4 precipitate is finally generated in the solution, and stirring is stopped until no more precipitate is generated in the solution. GO is separated by centrifugation at a speed of 720r / min and washed with water to remove residual impurities. - It is ultimately removed in the form of BaSO4 precipitation, greatly reducing the amount of water required for cleaning.

[0073] Step 4: Preparation of MFGO: Ultrasonic dispersion of 0.2 g of the washed GO powder obtained in step 3 in water to prepare 80 ml of graphene oxide dispersion; the obtained graphene oxide dispersion is added dropwise into 120 ml of anhydrous ethanol, and then 0.4 g of Fe3O4 magnetic material is added, stirred under ultrasonic action for 10 minutes, and then the mixed solution is freeze-dried to obtain MFGO.

[0074] Taking the MFGO prepared in Example 5 as an example, the typical pollutant methylene blue (MB) was selected as the target pollutant, and the adsorption performance of MFGO on MB was studied: the results showed that its initial adsorption capacity was 375.52 mg / g, and the adsorption capacity after 7 consecutive cycles was 312.50 mg / g.

[0075] Example 6

[0076] Step 1: Preparation of edge oxidation graphite intercalation mixture (EGOIC): The preparation of EGOIC by electrochemical edge oxidation intercalation is carried out using a two-electrode system in a vacuum environment, with graphite as the working electrode (anode) and platinum wire as the counter electrode (cathode). Then, 0.6 g of the graphite working electrode and the platinum wire counter electrode are placed in 120 mL of 85 wt.% H2SO4 solution, and the two are placed in parallel. A regulated DC power supply is used to apply a constant voltage of 12.5 V for edge oxidation. A small amount of OH in water in the H2SO4 solution is used to react with the graphite working electrode and the platinum wire counter electrode. - The ions gradually oxidize the graphite edge and open the graphite edge interlayer spacing until no bubbles are generated; then a constant voltage of 4V is applied for intercalation reaction, HSO4 - Gradually inserted into the graphite layers, the graphite gradually expands and turns blue, until the graphite turns completely blue, and EGOIC is obtained.

[0077] Step 2: Oxidation and stripping of EGOIC: The electrochemical oxidation and stripping of EGOIC is carried out using a two-electrode system, with 0.2g of EGOIC obtained in step 1 as the working electrode (anode) and a platinum wire as the counter electrode (cathode). Then, the EGOIC and the platinum wire are placed in 150mL of a Ba(OH)2 solution with a concentration of 0.1mol / L, and the two are placed in parallel. A constant voltage of 10V is applied with a regulated DC power supply to electrochemically oxidize and strip the EGOIC. As the reaction proceeds, GO gradually falls off and disperses in the solution until the EGOIC is completely stripped and the reaction stops.

[0078] Step 3: GO cleaning: The GO dispersed in the solution obtained in step 2 was stirred at a speed of 500 r / min. 2+ and HSO4 -BaSO4 precipitate is finally generated in the solution, and stirring is stopped until no more precipitate is generated in the solution. GO is separated by centrifugation at a speed of 720r / min and washed with water to remove residual impurities. - It is ultimately removed in the form of BaSO4 precipitation, greatly reducing the amount of water required for cleaning.

[0079] Step 4: Preparation of MFGO: Ultrasonic dispersion of 0.2 g of the washed GO powder obtained in step 3 in water to prepare 150 ml of graphene oxide dispersion; the obtained graphene oxide dispersion is added dropwise into 600 ml of anhydrous ethanol, and then 0.9 g of Fe3O4 magnetic material is added, stirred under ultrasonic action for 10 minutes, and then the mixed solution is freeze-dried to obtain MFGO.

[0080] Taking the MFGO prepared in Example 6 as an example, the typical pollutant methylene blue (MB) was selected as the target pollutant, and the adsorption performance of MFGO on MB was studied: the results showed that its initial adsorption capacity was 318.17 mg / g, and the adsorption capacity after 7 consecutive cycles was 265.02 mg / g.

[0081] Example 7

[0082] Step 1: Preparation of edge oxidation graphite intercalation mixture (EGOIC): The preparation of EGOIC by electrochemical edge oxidation intercalation is carried out using a two-electrode system in a vacuum environment, with graphite as the working electrode (anode) and platinum wire as the counter electrode (cathode). Then, 0.6 g of the graphite working electrode and the platinum wire counter electrode are placed in 120 mL of 85 wt.% H2SO4 solution, and the two are placed in parallel. A regulated DC power supply is used to apply a constant voltage of 12.5 V for edge oxidation. A small amount of OH in water in the H2SO4 solution is used to react with the graphite working electrode and the platinum wire counter electrode. - The ions gradually oxidize the graphite edge and open the graphite edge interlayer spacing until no bubbles are generated; then a constant voltage of 4V is applied for intercalation reaction, HSO4 - Gradually inserted into the graphite layers, the graphite gradually expands and turns blue, until the graphite turns completely blue, and EGOIC is obtained.

[0083] Step 2: Oxidation and stripping of EGOIC: The electrochemical oxidation and stripping of EGOIC is carried out using a two-electrode system, with 0.2 g of EGOIC obtained in step 1 as the working electrode (anode) and a platinum wire as the counter electrode (cathode). Then, the EGOIC and the platinum wire are placed in 150 mL of a 0.1 mol / L Ba(OH)2 solution, and the two are placed in parallel. A constant voltage of 10 V is applied with a regulated DC power supply to electrochemically oxidize and strip the EGOIC. As the reaction proceeds, GO gradually falls off and disperses in the solution until the EGOIC is completely stripped and the reaction stops.

[0084] Step 3: GO cleaning: The GO dispersed in the solution obtained in step 2 was stirred at a speed of 550 r / min. 2+ and HSO4 - BaSO4 precipitate is finally generated in the solution, and stirring is stopped until no more precipitate is generated in the solution. GO is separated by centrifugation at a speed of 760r / min and washed with water to remove residual impurities. - It is ultimately removed in the form of BaSO4 precipitation, greatly reducing the amount of water required for cleaning.

[0085] Step 4: Preparation of MFGO: Ultrasonic dispersion of 0.2 g of the washed GO powder obtained in step 3 in water to prepare 33 ml of graphene oxide dispersion; the obtained graphene oxide dispersion is added dropwise into 22 ml of anhydrous ethanol, and then 0.2 g of Fe3O4 magnetic material is added, stirred under ultrasonic action for 10 minutes, and then the mixed solution is freeze-dried to obtain MFGO.

[0086] Taking the MFGO prepared in Example 7 as an example, the typical pollutant methylene blue (MB) was selected as the target pollutant, and the adsorption performance of MFGO on MB was studied: the results showed that its initial adsorption capacity was 381.21 mg / g, and the adsorption capacity after 7 consecutive cycles was 319.81 mg / g.

[0087] It can be seen from the above embodiments that the magnetic crumpled graphene oxide adsorption material prepared by the scheme of the present application can effectively adsorb and recover pollutants, and can be recycled for more than 7 cycles, and its adsorption capacity is 84% ​​of the initial value, indicating that the MFGO prepared by the present application has good reusability.

Claims

1. A method for preparing a magnetic wrinkled graphene oxide adsorption material, characterized in that: The preparation steps include: (1) Preparation of edge-oxidized graphite intercalation mixture: Electrochemical edge-oxidized graphite intercalation was used to prepare the edge-oxidized graphite intercalation mixture. A two-electrode system was used in a vacuum environment. Graphite was used as the working electrode and platinum wire was used as the counter electrode. The graphite and platinum wire were then placed in a H2SO4 solution in parallel. A constant voltage was applied by a regulated DC power supply for edge oxidation. A small amount of OH in water in the H2SO4 solution was used to - The ions gradually oxidize the graphite edge and open the graphite edge interlayer spacing until no bubbles are generated; then a constant voltage is applied for intercalation reaction, HSO4 - Gradually inserting into the graphite interlayer, the graphite gradually expands and takes on a blue color, until the graphite turns completely blue, that is, an edge-oxidized graphite intercalation mixture is obtained; (2) Oxidation and exfoliation of the edge graphite oxide intercalation mixture: the edge graphite oxide intercalation mixture obtained in step (1) is used as a working electrode and a platinum wire is used as a counter electrode, and then the edge graphite oxide intercalation mixture and the platinum wire are placed in a Ba(OH)2 solution, with the two placed in parallel; a constant voltage is applied by a regulated DC power supply to electrochemically oxidize and exfoliate the edge graphite oxide intercalation mixture; as the reaction proceeds, graphene oxide gradually falls off and disperses in the solution until the edge graphite oxide intercalation mixture is completely exfoliated, and the reaction is stopped; (3) Cleaning of graphene oxide: The graphene oxide dispersed in the solution obtained in step (2) is stirred. 2+ and HSO4 - Finally, BaSO4 precipitate is generated in the solution, and stirring is stopped until no more precipitate is generated in the solution; then, the graphene oxide is separated by centrifugation and washed to remove residual impurities; (4) Preparation of magnetic wrinkled graphene oxide adsorption material: ultrasonically disperse the cleaned graphite oxide obtained in step (3) in water to prepare a graphene oxide dispersion, add the graphene oxide dispersion dropwise into anhydrous ethanol, and then add the magnetic material. After stirring for a period of time under ultrasonic action, the mixed solution is freeze-dried to obtain a magnetic wrinkled graphene oxide adsorption material.

2. The method for preparing a magnetic wrinkled graphene oxide adsorption material according to claim 1, characterized in that: The ratio of the graphite to the H2SO4 in step (1) is 0.3-0.9 g: 90-120 mL; the concentration of the H2SO4 in step (1) is 80-90 wt. %; the constant voltage for applying edge oxidation in step (1) is 10-15 V; and the constant voltage for applying intercalation reaction is 3-5 V.

3. The method for preparing a magnetic wrinkled graphene oxide adsorption material according to claim 1, characterized in that: The usage ratio of the edge oxide graphite intercalation mixture described in step (2) to the Ba(OH)2 solution is 0.1-0.3 g: 100-200 mL respectively.

4. The method for preparing a magnetic wrinkled graphene oxide adsorption material according to claim 1, characterized in that: In step (2), the concentration of the Ba(OH)2 solution is 0.05-0.2 mol / L.

5. The method for preparing a magnetic wrinkled graphene oxide adsorption material according to claim 1, characterized in that: The constant voltage applied in step (2) is 8-12V.

6. The method for preparing a magnetic wrinkled graphene oxide adsorption material according to claim 1, characterized in that: In step (3), the stirring speed is 300-600 r / min, and the centrifugal speed is 500-1000 r / min.

7. The method for preparing a magnetic wrinkled graphene oxide adsorption material according to claim 1, characterized in that: In step (4), the usage ratio of the graphene oxide dispersion, the magnetic material, and anhydrous ethanol is 33-150 mL: 0.2-0.9 g: 22-600 mL.

8. The method for preparing a magnetic wrinkled graphene oxide adsorption material according to claim 1, characterized in that: In step (4), the concentration of the graphene oxide dispersion is 2-3 mg / mL; in step (4), the volume ratio of the graphene oxide dispersion to anhydrous ethanol is 0.25-1.5:

1.

9. The method for preparing a magnetic wrinkled graphene oxide adsorption material according to claim 1, characterized in that: The magnetic material described in step (4) is at least one of Fe3O4, NiO, and CoO; the stirring time described in step (4) is 5-15 minutes.

10. An application of a magnetic wrinkled graphene oxide adsorption material, characterized in that: Used in environmental protection and composite materials fields.